Case report: Successful surgical resection of an intracranial frontal lobe dermoid cyst in a cat - Nakano, Yukiko; Nozue, Yuta; Hazeyama, Hiromi; Matsunami, Tokio; Chambers, James; Uchida, Kazuyuki; Kobatake, Yui (Frontiers in Veterinary Science, 2025)
IntroductionIntracranial dermoid cysts (IDCs) are rarely observed in veterinary medicine, and reports regarding treatment strategies for feline IDCs are severely lacking. This report describes the surgical management of epileptic seizures caused by IDCs in a cat.Case presentationAn 8-year-old, spayed, female American Shorthair cat presented with epileptic seizures. The epileptic seizures, which had developed at the age of 5 years, had been controlled by phenobarbital administration. At 8 years old, the cat contracted acute hepatitis, prompting a switch from phenobarbital to other antiseizure medications. This drug switch caused an increase in the frequency of epileptic seizures. Magnetic resonance imaging (MRI) revealed a dermoid cyst as a heterogeneous intensity mass on T2-weighted images, without falx cerebri displacement. The preoperative seizures occurred more than three times a day (cluster seizures), even though the cat was administered multiple antiseizure medications. The seizures ceased after surgical removal of the dermoid cyst. The cat did not experience seizures for 14 months after surgery, even with discontinuation of antiseizure medications.ConclusionIn cats, surgical removal of frontal lobe IDCs may effectively control epileptic seizures without fatal complications, thus potentially leading to a great prognosis.